IMPLEMENTASI SISTEM PENGENALAN WAJAH UNTUK KEAMANAN AKSES BERBASIS UBUNTU MENGGUNAKAN PYTHON - Fahrizal fahrizal fahrizal (Jurnal Informatika, 2021)
Security is one of the most important needs for human beings in both the building and the house. For the development of security technology used face recognition. Face recognition is a system that identifies facial features that are capable of detecting familiar faces and unknown faces. In this research is implemented with computer vision where the computer can see and understand so that it is information from an image or video. This computer can also mimic the ability of human intelligence. To classify a face object, OpenCv uses the Haar Cascade classifier and uses Python programming language. Application used face Recognition program is PyCharm Comunity 2018 version 3 with Linux operating system Ubuntu 18.04.2 LTS version. The results showed that the accuracy of face reconition depends on the analysis of OpenCv and the classification of Cascade for computer vision process.